A Pt-based intermetallic ordered alloy, preparation method and application
By wrapping a heteroatom-rich encapsulation layer on the support and performing pyrolysis, the problem of difficult to take into account high activity and high stability between Pt-based metals is successfully solved, and efficient catalyst synthesis is achieved, which significantly improves ORR activity. and fuel cell performance.
Patent Information
- Application Number
- CN202210845558.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-07-19
AI Technical Summary
The synthesis of ordered alloys between Pt-based metals is difficult to take into account both high activity and high stability, and the amount of cathode Pt catalyst in the prior art is too high and it is expensive.
By uniformly wrapping a layer of heteroatom-rich encapsulation on the carrier and pyrolysis is performed under a specific atmosphere, small particle size and high dispersion Pt-M intermetal ordered alloy particles are obtained, achieving high activity and high stability Sexual consideration.
This method greatly shortens the formation time and formation temperature of intermetallic ordered alloys, avoids particle agglomeration, and the resulting catalyst has high oxygen reduction reaction (ORR) activity and hydrogen air fuel cell performance, which is far better than commercial Pt/C Catalysts while maintaining the stability of the support.
Smart Images

Figure CN115172785B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the synthesis of electrocatalysts, chemical synthesis and fuel cell technology, and specifically proposes a Pt-based intermetallic ordered alloy and a synthesis method thereof, and application thereof in fuel cells. Background Art
[0002] Proton exchange membrane fuel cells have the advantages of being clean, pollution-free, and having a low operating temperature, and they occupy an important position in the energy structure of future society. However, proton exchange membrane fuel cells still have problems such as excessive use of cathode Pt catalysts and high prices. Developing low-Pt oxygen reduction electrocatalysts is one of the most effective ways to reduce the Pt loading of the catalyst. Pt-based metal ordered alloy catalysts are considered to be the next generation of low-Pt oxygen reduction electrocatalysts. However, the synthesis of Pt-based metal ordered alloys still faces a series of difficulties, which makes it difficult for Pt-based metal ordered metal alloys to have both high activity and high stability. Summary of the invention
[0003] The present invention provides a Pt-based intermetallic ordered alloy and a synthesis method thereof, which can significantly shorten the formation time and temperature of the intermetallic ordered alloy, avoid particle agglomeration, and maintain the stability of the carrier, ultimately taking into account both the high activity and high stability of the Pt-based alloy catalyst.
[0004] The present invention is achieved in that:
[0005] A method for synthesizing a Pt-based intermetallic ordered alloy, the specific steps are as follows:
[0006] Step 1, uniformly coating a coating layer rich in heteroatoms on the carrier to obtain a carrier with a coating layer;
[0007] Step 2: mixing a precursor containing PtM with a carrier having a coating layer, or directly loading disordered PtM alloy particles on the carrier having a coating layer, to obtain a precursor catalyst, wherein M is a transition metal;
[0008] Step three, thermally decomposing the precursor catalyst under a specific atmosphere to obtain a Pt-based ordered alloy catalyst.
[0009] As a further improvement, the present invention further provides a Pt-based intermetallic ordered alloy.
[0010] As a further improvement, the present invention further provides a Pt-based intermetallic ordered alloy fuel cell, which is made from the above-mentioned Pt-based intermetallic ordered alloy.
[0011] The beneficial effects of the present invention are:
[0012] 1) The present invention constructs a coating layer rich in heteroatoms on the carrier, accurately controls the thickness of the coating layer, and then loads disordered alloy particles or mixed Pt alloy precursors for high-temperature pyrolysis. The non-metal in the coating layer rich in heteroatoms with a thickness of ≤5nm anchors the Pt particles to prevent further agglomeration of the Pt particles, while regulating the electronic structure of the surface of the PtM particles. The synergistic effect of such a dual-functional mechanism can effectively inhibit the agglomeration of PtM particles, reduce the particle size of the PtM intermetallic ordered alloy to 3nm, and greatly reduce the pyrolysis time and pyrolysis temperature of the alloy catalyst, thereby obtaining small-size, highly dispersible Pt-M intermetallic ordered alloy particles, ultimately taking into account both the high activity and high stability of the Pt-based alloy catalyst.
[0013] 2) The synthesis method of the present invention can greatly shorten the time and temperature of high-temperature phase transformation, reduce the heat treatment time to 1h, and reduce the heat treatment temperature to 600°C; at the same time, the obtained PtM intermetallic compound has a high degree of order, and the purity of the ordered phase is close to 100%. The synthesized catalyst has high ORR activity and hydrogen-air fuel cell performance, which is far superior to commercial Pt / C catalysts; and the introduction of the encapsulation layer does not reduce the stability of the carrier, and the stability of the carrier is basically maintained. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The statistical distribution of TEM particle size of the carbon carriers of Example 1, Control Experiment 1 and Control Experiment 2, Control Experiment 3, Control Experiment 4, Control Experiment 5, and Control Experiment 6.
[0016] Figure 2 TEM and particle size statistical distribution diagram of the catalyst in Example 1.
[0017] Figure 3 The XRD diagrams of the catalysts in Example 1 and Control Experiment 1 are shown in FIG.
[0018] Figure 4 It is a comparison chart of the activities of Example 1, Control Experiment 1 and Control Experiment 2, Control Experiment 3, Control Experiment 4, Control Experiment 5, Control Experiment 6, and commercial Pt / C on hydrogen-air fuel cells.
[0019] Figure 5It is a stability comparison chart of Example 1, Control Experiment 1 and Control Experiment 2, Control Experiment 3, Control Experiment 4, Control Experiment 5 and Control Experiment 6 on a hydrogen-air fuel cell. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0022] A method for synthesizing a Pt-based intermetallic ordered alloy, the specific steps are as follows:
[0023] Step 1, uniformly coating a coating layer rich in heteroatoms on the carrier to obtain a carrier with a coating layer;
[0024] Step 2: mixing a precursor containing PtM with a carrier having a coating layer, or directly loading disordered PtM alloy particles on the carrier having a coating layer, to obtain a precursor catalyst, wherein M is a transition metal;
[0025] Step three, thermally decomposing the precursor catalyst under a specific atmosphere to obtain a Pt-based ordered alloy catalyst.
[0026] As a further improvement, the heteroatom-rich encapsulation layer is formed by a C layer doped with any one or several non-metallic elements such as N, P, and S. On the one hand, the elements such as N, P, and S in the encapsulation layer can anchor the Pt particles during the heat treatment process to prevent further agglomeration of the Pt particles and improve the activity of the catalyst. On the other hand, the encapsulation layer does not contain metal elements and will not produce metal residue problems in the subsequent pyrolysis process, thereby ensuring good stability of the catalyst.
[0027] As a further improvement, the thickness of the heteroatom-rich encapsulation layer is controllable, and its thickness is ≤5nm. Preferably, the thickness of the encapsulation layer is 5nm. The elements such as N, P, and S in the encapsulation layer can anchor Pt and regulate the electronic structure of the surface of the PtM particles. Through such a dual-functional mechanism, the agglomeration of PtM particles can be effectively suppressed, so that the particle size of the PtM intermetallic ordered alloy is reduced to 3nm, and the ORR reaction activity is improved. The effect of the encapsulation layer with a thickness of 5nm is optimal. When there is no encapsulation layer, the ORR activity deteriorates due to the lack of anchoring elements; and when the thickness of the encapsulation layer is greater than 5nm, there are more N, P, and S sites in the overly thick encapsulation layer, which will bring more instability, causing the catalyst stability to drop significantly.
[0028] As a further improvement, in step 1, one or more of the precursors of the coating layer containing any one of non-metallic materials such as N, P, S, or one or more of the precursors of the coating layer containing several non-metallic materials such as N, P, S, and the carrier are added to the solvent at a mass ratio of 1:2-4 and stirred, and the solvent is evaporated and then heat-treated under a specific atmosphere, so as to obtain a coating layer uniformly coated with a layer of non-metallic doped C on the surface of the carrier. Preferably, the preparation steps of the coating layer rich in heteroatoms are as follows: any one or more of melamine, tetraphenylphosphine chloride, dithiophene, etc., and the carrier are dissolved and dispersed in a mixed solution at a mass ratio of 1:2-4 and stirred overnight, and the mixed solution is prepared by ethanol and water at a mass ratio of 1:1-2, and then the solvent is evaporated to obtain a black powder, and the black powder is heat-treated under a specific atmosphere, that is, a coating layer uniformly coated with a layer of non-metallic doped C on the surface of the carrier. More preferably, the mass ratio of any one or more of melamine, tetraphenylphosphine chloride, dithiophene and the like to the carrier is 1:2.5, and the doping amount of any one or more of non-metals such as N, P, S is optimally about 1%. Too high a doping amount will reduce the graphitization degree of the carrier and reduce stability; too low a doping amount will not play an anchoring role. Too high or too low a ratio of ethanol to water will lead to poor dispersion of melamine, tetraphenylphosphine chloride, dithiophene and the like in carbon, resulting in an uneven coating layer.
[0029] As a further improvement, in step 1, the specific steps of the heat treatment are: heat treatment at a temperature of 600-900°C in an argon or hydrogen atmosphere for 1.5-2.5 hours. The preparation process conditions of the coating layer affect the thickness of the coating layer. The longer the heat treatment time, the thinner the coating layer will be due to pyrolysis and volatilization; if the heat treatment time is too short, the thickness of the formed coating layer cannot meet the requirements. The thickness of the coating layer can be precisely controlled by synergistically adjusting and controlling the addition of the coating layer precursor and the preparation process conditions of the coating layer.
[0030] As a further improvement, the carrier is any one of a carbon carrier, an inert metal oxide, and a metal carbide.
[0031] As a further improvement, in step 2, M is any one or more of transition metals such as Fe, Co, Ni, Cu, Zn, Pd, Ru, Mo, etc. Specifically, the precursor of PtM or the PtM alloy particles are PtCo, PtFe, PtNi, PtZn alloy, etc.
[0032] As a further improvement, in step 2, specifically: the carrier with a coating layer and the precursor containing PtM or PtM alloy particles are uniformly dispersed in a mixed solution in a mass ratio of 1 to 3:1, and the mixed solution is prepared by ethanol and water in a mass ratio of 1:1 to 2, and then the solvent is evaporated to obtain a precursor catalyst Pre-PtM / TC (T is N or / and P or / and S); preferably, in the embodiment, the mass ratio of the carrier with a coating layer to the precursor containing PtM or PtM alloy particles is 1.5:1; too high a mass ratio of the carrier with a coating layer and the precursor containing PtM (or PtM alloy particles) will lead to less PtM precursor and reduced catalytic activity, while too low a mass ratio will lead to uneven dispersion of the precursor containing PtM (or PtM alloy particles). Too high or too low a ratio of ethanol to water will lead to poor dispersibility of the precursor containing PtM (or PtM alloy particles).
[0033] As a further improvement, in step three, specifically: heat treatment for 1 to 1.5 hours at a temperature of 550 to 650°C and in a 4 to 6% H2 / Ar mixed atmosphere to obtain a Pt-based ordered alloy catalyst, wherein too low a H2 concentration will result in insufficient reducing atmosphere, and too high a concentration will result in safety hazards; wherein the content of precious metals is between 25-30wt%. Further preferably, the precursor catalyst Pre-PtM / TC is heat treated for 1 hour at a temperature of 600°C in a 5% H2 / Ar mixed atmosphere. Too high a temperature will cause PtM particles to agglomerate, affecting the catalytic activity of the fuel cell, and too low a temperature will result in the failure to form a PtM metal ordered alloy. Similarly, too long a heat treatment time will cause PtM particles to agglomerate, affecting the catalytic activity of the fuel cell, and too short a treatment time will result in the failure to form a PtM metal ordered alloy.
[0034] As a further improvement, an embodiment of the present invention further provides a method for rapidly forming an ordered Pt-based intermetallic alloy.
[0035] As a further improvement, an embodiment of the present invention further provides a fuel cell for rapidly forming a Pt-based metal ordered alloy, which is made from the above-mentioned Pt-based metal ordered alloy.
[0036] Specific examples: (Unless otherwise specified, the raw materials and catalysts in the examples of this application are purchased through commercial channels).
[0037] Example 1
[0038] (1) Weigh 200 mg of melamine and 500 mg of carbon black and uniformly disperse them in a 1:1 mixture of ethanol and water. After being uniformly dispersed by ultrasonication, stir overnight. Then, the solvent is evaporated by rotary evaporation to obtain a black powder.
[0039] (2) The black powder synthesized in step (1) was heat treated at 800° C. in an argon atmosphere for 2 h, and a N-doped C coating layer was uniformly coated on the surface of the carrier. The thickness of the coating layer was about ≤5 nm, and then TEM characterization was performed.
[0040] (3) 40 mg of the carrier synthesized in step (2), 40 mg of platinum acetylacetonate, and 33 mg of cobalt acetylacetonate were uniformly dispersed in a mixture of ethanol and water in a ratio of 1:1, and then ultrasonically dispersed and stirred overnight, and then the solvent was evaporated by rotary evaporation to obtain a precursor catalyst Pre-PtCo / NC;
[0041] (4) Pre-PtCo / NC was heat treated at 600 °C in a 5% hydrogen and argon atmosphere for 1 h to obtain the final catalyst O-PtCo / NC (5 nm wrapping layer) with a Pt content of 27.7 wt% (determined by ICP-OES);
[0042] (5) The O-PtCo / NC catalyst was characterized by TEM and XRD.
[0043] (6) Weigh 20 mg of O-PtCo / NC and 37 mg of nafion 2020 and ultrasonically disperse them in a mixture of isopropanol and water in a mass ratio of 4:1. Weigh 20 mg of commercial Pt / C and 40 mg of nafion 2020 and ultrasonically disperse them in a mixture of isopropanol and water in a mass ratio of 4:1.
[0044] (7) A 12 μm GORE membrane was selected as the proton exchange membrane, and the catalyst in step (4) was evenly sprayed on both sides of the proton exchange membrane using an ultrasonic spraying method. The anode catalyst was commercial Pt / C with a loading of 0.05 mg. Pt cm -2 The cathode catalyst is O-PtCo / NC with a loading of 0.1 mg Pt cm -2 , and then assembled into a single cell together with the gas diffusion layer.
[0045] (8) The membrane electrode prepared in step (7) was assembled into a battery and a single cell test was performed. The test conditions were: Scribner 850e test system; anode: 100% humidified hydrogen, 0.5 back pressure; cathode: 100% humidified air, 0.5 back pressure.
[0046] Control experiment 1 of Example 1:
[0047] The synthesis and fuel cell test were carried out using the method of Example 1, except that melamine was not added in step (1) and the heat treatment time in step (4) was changed to 5 h. The synthesized catalyst was O-PtCo / NC (without a coating layer).
[0048] Control experiment 2 of Example 1:
[0049] The method of Example 1 was used for synthesis and fuel cell testing, except that the amount of melamine added in step (1) was 100 mg, and the heat treatment time in step (2) was changed to 2.5 h, and the temperature remained unchanged. The synthesized catalyst was O-PtCo / NC (2.5 nm coating layer).
[0050] Control experiment 3 of Example 1:
[0051] The synthesis and fuel cell test were carried out using the method of Example 1, except that the amount of melamine added in step (1) was 400 mg, and the heat treatment time in step (2) was changed to 1.5 h, and the temperature remained unchanged. The synthesized catalyst was O-PtCo / NC (10 nm coating layer).
[0052] Control experiment 4 of Example 1:
[0053] The synthesis and fuel cell test were carried out using the method of Example 1, except that the amount of melamine added in step (1) was 600 mg, and the heat treatment time in step (2) was changed to 1 h, and the temperature remained unchanged. The synthesized catalyst was O-PtCo / NC (20 nm coating layer).
[0054] Control experiment 5 of Example 1:
[0055] The method of Example 1 was used for synthesis and fuel cell testing, except that the amount of melamine added in step (1) was 800 mg, and the heat treatment time in step (2) was changed to 0.5 h, and the temperature remained unchanged. The synthesized catalyst was O-PtCo / NC (30 nm coating layer).
[0056] Control experiment 6 of Example 1
[0057] The method of Example 1 was used for synthesis and ORR and fuel cell testing, with the following differences: step (1) 1.2 g zinc nitrate hexahydrate, 1.314 g 2-methylimidazole and carbon black were weighed and dissolved in 100 ml methanol, mixed after full dissolution, and reacted for 8 h under magnetic stirring at room temperature. The stirred mixed solution was then centrifuged to separate the waste liquid to obtain a black solid, which was then ultrasonically washed with methanol 3 times and then vacuum dried overnight. Step (2) The dried black powder in step (1) was heat treated at 1100°C for 1 h under an Ar gas atmosphere to obtain a carrier with a 50 nm coating layer, which was then characterized by TEM. The synthesized catalyst is O-PtCo / NC (50 nm coating layer). (Note: A coating layer of this thickness cannot be synthesized by the melamine method and needs to be synthesized using the above method. The final result only changes the thickness of the coating layer without changing other factors.)
[0058] Control experiment 7 of Example 1:
[0059] Fuel cell testing was performed using a commercial Pt / C catalyst.
[0060] The TEM particle size distribution diagrams of the carbon carriers of Example 1, Control Experiment 1, Control Experiment 2, Control Experiment 3, Control Experiment 4, Control Experiment 5, and Control Experiment 6 are shown in FIG. Figure 1 As shown in the figure, the average particle size of the carbon carriers in the embodiment and the control experiment can be known from the particle size distribution diagram. Furthermore, the thickness of the coating layer is equal to the average particle size of the carbon carrier after coating minus the average particle size of the carbon carrier before coating. The specific thickness of the coating layer can be calculated by the above method. At the same time, it can be known that as the amount of melamine increases, the coating layer gradually becomes thicker. Figure 1 It can be seen that changing the wrapping layer synthesis method can effectively obtain a wrapping layer of a certain thickness. Figure 2 The TEM and particle size statistics of the catalyst of Example 1 are shown. It can be seen that after the 5nm coating layer treatment, the particle size of the PtCo intermetallic ordered alloy is only 3nm and highly dispersed, which can show that this method can synthesize a commercially valuable PtCo catalyst. The XRD diagrams of the catalysts of Example 1 and Control Experiment 1 are shown in Figure 3 As shown in the figure, with a 5nm encapsulation layer, a highly ordered intermetallic ordered alloy can be obtained after only 1h of heat treatment, and the degree of order is close to 100%. When there is no encapsulation layer, a highly ordered intermetallic ordered alloy can be obtained after 5h of heat treatment, and the degree of order is not high. This shows that the 5nm encapsulation layer can promote the accelerated transformation of the intermetallic ordered alloy. Figure 4 The hydrogen-air fuel cell activity diagrams of Example 1, Control Experiment 1, Control Experiment 2, Control Experiment 3, Control Experiment 4, Control Experiment 5, Control Experiment 6, and commercial Pt / C are shown. The performance of the catalyst in Example 1 can reach 1.4 W cm at 0.6 V. -2, much higher than commercial Pt / C. At the same time, the power density at 0.6V also gradually increases with the thickness of the coating layer, reaching the highest at 5nm. The power density slightly decreases with the increase of the coating layer thickness. Figure 5 As shown in the figure, after the 5nm coating treatment, the stability of the catalyst fuel cell is around 0.8A cm -2 The voltage attenuated only 36mV, and the stability gradually deteriorated as the coating became thicker. The reason for the deterioration is that the high-content N-containing carrier will decompose due to the high potential during the electrocatalytic ORR reaction, resulting in great instability. In summary, the 5nm coating layer can not only improve the activity of the fuel cell but also retain high stability.
[0061] In other embodiments, the PtM-containing precursor or the PtM alloy particles may be an alloy of Pt and other transition metals, such as any one of PtFe, PtNi, and PtZn.
[0062] In the above embodiments, the content of the precious metal is between 25-30 wt %.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a Pt-based ordered intermetallic alloy, characterized in that: The specific steps are as follows: Step 1: uniformly wrapping a layer of heteroatom-rich wrapping layer on the carrier to obtain a carrier with a wrapping layer, wherein the heteroatom-rich wrapping layer has a thickness of ≤5nm; the heteroatom-rich wrapping layer is formed by a C layer doped with any one or several non-metallic elements such as N, P, and S, and the wrapping layer does not contain metal elements; the carrier is a carbon carrier; Step 2: mixing a precursor containing PtM with a carrier having a coating layer, or directly loading disordered PtM alloy particles on the carrier having a coating layer, to obtain a precursor catalyst, wherein M is a transition metal; Step three, pyrolyzing the precursor catalyst at a temperature of 550-600° C. in a H 2 / Ar mixed atmosphere to obtain a Pt-based ordered alloy catalyst.
2. The method for synthesizing a Pt-based intermetallic ordered alloy according to claim 1, characterized in that: In step 1, one or more non-metallic coating layer precursors containing any one of N, P, and S, or one or more non-metallic coating layer precursors containing N, P, and S, and a carrier are added to a solvent at a mass ratio of 1:2 to 4 and stirred. After evaporating the solvent, heat treatment is performed in an argon or hydrogen atmosphere to obtain a coating layer uniformly coated with a non-metallic doped C on the surface of the carrier.
3. The method for synthesizing a Pt-based intermetallic ordered alloy according to claim 2, characterized in that: The encapsulating layer precursor is one or more of melamine, tetraphenylphosphine chloride and dithiophene.
4. The method for synthesizing a Pt-based intermetallic ordered alloy according to claim 2, characterized in that: In step 1, the specific steps of the heat treatment are: heat treatment at a temperature of 600 to 900° C. in an argon or hydrogen atmosphere for 1.5 to 2.5 hours.
5. A Pt-based intermetallic ordered alloy, characterized in that: Prepared by the method described in any one of claims 1 to 4.
6. A Pt-based intermetallic ordered alloy fuel cell, characterized in that: It is prepared from the Pt-based intermetallic ordered alloy prepared according to any one of claims 1 to 4.
Citation Information
Patent Citations
Graphitized carbon layer confined multi-element platinum alloy catalyst and preparation method thereof
CN112563523A